Book review on tahfiz education and soft skills by Dr. Rashidi Abbas in Sharing@BookCafe programme - Noorul Farina, Arifin (2019)
Universiti Malaysia Pahang (UMP) Library held a programme, ‘Sharing@BookCafe’, aimed at promoting reading and making reading part of one’s lifestyle and at hand to impart the experience was none other than Dr. Rashidi Abbas, the recipient of the National Book Award for general book in the education category. Dr. Rashidi Abbas, a senior lecturer at Centre for Modern Languages & Human Science (CMLHS), did a review on a book titled, ‘Pendidikan Tahfiz dan Kemahiran Insaniah’ (Tahfiz Education and Soft Skills) at the event held on April 18, 2019.